Large Urban Developments as Non-Planning Products: Conflicts and Threats for Spatial Planning - Ioannou, Byron (2019)
The article approaches different concepts of Large Urban Developments (LUDs) as products of the notion of a “spatial fix” (Harvey, 2001), which explains why built or natural environments can be deployed in the process of creating opportunities for new investments. Greece and Cyprus are two countries in the south of the European Union that underwent delayed urbanisation and significant land fragmentation in the form of small size private ownerships and with limited experience in comprehensive development. Greece has adopted a well-structured but complex spatial planning system, bureaucratic with limited effectiveness, adaptability or flexibility of delivery processes. On the other hand, Cyprus has a flexible but centralized system, effective in processing change but problematic in regulating quality in the built environment. Both countries recently experienced major financial crises. In the early 2010s, both governments promoted, as part of an economic recovery policy, extensive real estate development on public or privately-owned land with emphasis on LUDs as ways of addressing economic shortfalls. Inappropriately, LUDs have been primarily “conceived” as opportunities to attract foreign investments rather than a means of tackling crucial current deficiencies. New spatial planning frameworks merely add greater “flexibility” to the system in order to accelerate large private real estate investment. The article attempts to reveal, through case studies’ reviews, the impact of LUDs in countries with no infrastructure or experience in accommodating large-scale investment. It explores how the experience in Greece and Cyprus differs in terms of the relevant legislation adopted, the effectiveness in fulfilling its primary objective in attracting investment, and what are the possible social and environmental consequences on the planning acquis.